INFLAMMATORY MEDIATORS ROLE IN ATHEROSCLEROTIC LESION DEVELOPMENT IN THE LARGE ARTERIES IN PATIENTS WITH SYSTEMIC SCLERODERMIA - A. L. Maslyansky; E. P. Kolesova; A. V. Kozlenok; E. Yu. Vasilieva; I. N. Penin; O. P. Rotar; N. M. Lazareva; S. V. Lapin; K. A. Sysoev; V. N. Solntsev; A. N. Bazhenov; A. O. Konradi (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the prevalence of atherosclerosis, to define the type of atherosclerotic lesion of brachiocephalic arteries in patients with systemic sclerodermia (SSD); to reveal the main factors influencing that process.Material and methods. Totally 38 patients with SSD studied. We measured vessel stiffness on the area between carotid and femoral arteries; instrumental and laboratory characteristics of endothelial function, morphology of carotid arteries, lipid profile parameters, as glucose, uric acid, N-terminal brain natriuretic peptide (NT-proBNP), antinuclear autoantibodies spectrum, cytokines concentration and chemokines of serum.Results. The increase of intima-media thickness (IMT) was found in 79% (n=30/38) of the patients studied with SSD. In one of the patients there was occluded carotid artery. Different level of arterial stenosis (20- 70%) — in 52,6% (n=20/38) of patients. We also measured relation of IMT and several classic risk factors (RF) of atherosclerosis (age, glyciemia level). Among non-classical risk factors there was relation of IMT and levels of asymmetrical dimethyl arginine (ADMA), soluble adhesion endothelium molecule (sVCAM), uric acid, NT-proBNP, autoantibodies to centromeres proteines. In multiple regression analysis the most informative predictors of IMT were age, uric acid, sVCAM, granulocytic colony- stimulating factor (G-CSF) and interleucine-1 (IL-1). Conclusion. In SSD patients atherosclerosis develops partially through non-classic factors influence, primarily inflammatory mediators and common for SSD metabolic disruptions (uricemia). This can point on the specific interrelation of pathogenetic mechanisms of arterial wall involvement in SSD, and might require repeated assessment of IMT in SSD, using larger patients selection and additional investigation methods.